DAMPAK MOBILITAS ULANG ALIK TERHADAP PENDAPATAN RUMAH TANGGA PETANI DI KABUPATEN KARANGANYAR - Nuning Setyowati (Universitas Sebelas Maret, 2009)
The aim of the research is to know the factor which motivate commutation and its effect to labour farm household supply. The result show that factors which cause commutation are: (a) support factor: temporer farming and small field (2.214 m2), low farming income (Rp 4.624.040/year), limited chance to work in village and strategic location of village; (b) unsupported factor: expensive transport cost and safeti; (c) interesting factor: variated occupation with high wage in big city and full fasilitation; (d) individual factor: the people in productive years and education level relevant with the job. Finally, by commutation proved have effect to increase the income of farm household.